Enhanced microwave absorption properties of flake-shaped FeCo/BaFe12O19 composites. Issue 9 (1st May 2021) - Gong, Haonan; Tan, Shujuan; Zheng, Jing; Peng, Kangsen; Zhang, Yanting; Hu, Yunjia; Duan, Songhan; Xu, Guoyue
Abstract: In this work, flake-shaped FeCo/BaFe12 O19 composites were successfully prepared via a facile two-step process involving ball milling and sol-gel treatment. Compared with commonly used FeCo alloys, FeCo/BaFe12 O19 composite material can achieve remarkable microwave absorption performance, and this is largely because of the flake-shaped structure and dielectric relaxation processes. Furthermore, changing mass fractions of BaFe12 O19 enable flexible control of applicable frequency ranges of FeCo/BaFe12 O19 composites. It was found that when the BaFe12 O19 mass fraction is as high as 20%, minimum reflection loss can reach −51.22 dB with effective loss of < –10 dB and effective bandwidth of 6.24 GHz even at a thin thickness of 1.45 mm. It is highly believed that these significant achievements will arouse interest from researchers for further practical exploration of microwave absorbers.